2024
DOI: 10.3390/ma17051092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Modification of Polycarboxylate Superplasticizers—A Review

Yuchen Xia,
Wei Shi,
Shuncheng Xiang
et al.

Abstract: The molecular-scale structural changes in polycarboxylic superplasticizer (PCE) can influence dispersion and water retention. Polycarboxylate superplasticizer, synthesized using different methods, may alter dispersion and water-reducing effects. The synthesis of PCE involves creating a novel macromolecular monomer with a controllable molecular mass, adjustable lipophilic, and hydrophilic moieties, as outlined in this study. This article reviews processes for synthesizing polycarboxylates and identifies the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Previous research [ 25 , 26 , 27 , 28 , 29 ] has demonstrated that a polymer derivative of polycarboxylate ether can effectively serve as a superplasticizer, enhancing the workability of fresh mortar augmenting its fluidity. This obviates the necessity for excessive mixing water and allows for fine-tuning the paste’s fluidity to attain a more easily manageable consistency.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [ 25 , 26 , 27 , 28 , 29 ] has demonstrated that a polymer derivative of polycarboxylate ether can effectively serve as a superplasticizer, enhancing the workability of fresh mortar augmenting its fluidity. This obviates the necessity for excessive mixing water and allows for fine-tuning the paste’s fluidity to attain a more easily manageable consistency.…”
Section: Introductionmentioning
confidence: 99%